The Effect of Fiscal Loss Compensation, Sales Growth, Transfer Costs on Tax Avoidance Moderated by CSR - Jhon Raphael Saragih; Latersia Br Gurusinga; Andy Prashetyo (International Journal of Economics and Management Research, 2025)
This study focuses on the impact of fiscal loss compensation, sales growth, and transfer pricing on tax avoidance moderated by Corporate Social Responsibility (CSR) in companies listed in the LQ45 Index of the Indonesia Stock Exchange during the period of 2019-2023. The sources of this research come from data on companies listed in the LQ45 Index, which is a collection of high liquidity companies on the Indonesia Stock Exchange. This study aims to provide insight into how these factors interact and influence tax avoidance in Indonesia, which is an important issue considering the low tax ratio in this country. Data analysis was conducted using multiple linear regression tests. The research results indicate that partially, fiscal loss compensation has a negative and significant impact on tax avoidance, sales growth has a negative and insignificant impact on tax avoidance, and Transfer pricing has a positive but insignificant effect on tax avoidance. Simultaneously, fiscal loss compensation, sales growth, and transfer pricing have a positive but insignificant effect on tax avoidance. Based on the moderated regression analysis (MRA), CSR can influence the relationship between fiscal loss compensation and tax avoidance, CSR cannot influence the relationship between sales growth and tax avoidance, and CSR cannot influence transfer pricing and tax avoidance.